2020
DOI: 10.1093/femspd/ftaa061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2 RT-PCR on a high-throughput molecular diagnostic platform and the cobas SARS-CoV-2 test for the diagnostic of COVID-19 on various clinical samples

Abstract: Objectives In order to cope with the rapid spread of the COVID-19 pandemic, we introduced on our in-house high-throughput molecular diagnostic platform (MDx Platform) a real-time reverse transcriptase PCR (RT-PCR) to detect the SARS-CoV-2 from any clinical specimens. The aim of this study was to compare the RT-PCR results obtain with the MDx Platform and the commercial assay cobas SARS-CoV-2 (Roche) on nasopharyngeal swab and other clinical specimens including sputum, bronchial aspirate, bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…To investigate the impact of the method and operator on Ct estimates, samples containing 1-100’000 SARS-CoV-2-C2 g.c.p.r. were analysed by RT-qPCR in two independent labs using different assays (30,31). We found that the Ct values obtained from these samples using independent methods are highly correlated ( Figure S4A, Additional File 1 ) as previously found (32).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the impact of the method and operator on Ct estimates, samples containing 1-100’000 SARS-CoV-2-C2 g.c.p.r. were analysed by RT-qPCR in two independent labs using different assays (30,31). We found that the Ct values obtained from these samples using independent methods are highly correlated ( Figure S4A, Additional File 1 ) as previously found (32).…”
Section: Resultsmentioning
confidence: 99%
“…Given the uncertainty regarding sensitivity and specificity of RAT, all antigen results were confirmed on one of the following molecular platforms: i) VIASURE SARS-CoV-2 (N1 + N2) Real Time PCR Detection Kit for BD MAX™ (Becton Dickinson, USA) or GeneXpert SARS-CoV-2 test (Cepheid, https://www.cepheid.com) 12 as rapid systems, ii) test cobas 6800® SARS-CoV-2 (Roche, Basel, Switzerland) 13 or our automated high-throughput molecular diagnostic (MDx) platform as classic systems. Our MDx platform uses Magnapure RNA-extraction coupled to applied biosystems 7900 amplification device (Quant Studio 7) and three Hamilton robots, with primers targeting the E- and RdRp-encoding genes 14,15 .…”
Section: Methodsmentioning
confidence: 92%
“…Real Time PCR Detection Kit for BD MAX™ (Becton Dickinson, USA) or GeneXpert SARS-CoV-2 test (Cepheid, https://www.cepheid.com) 12 as rapid systems, ii) test cobas 6800® SARS-CoV-2 (Roche, Basel, Switzerland) 13 or our automated high-throughput molecular diagnostic All rights reserved. No reuse allowed without permission.…”
Section: Routine Confirmation By Rt-pcrmentioning
confidence: 99%
“…Viral load were obtained by converting cycle thresholds of the RT-PCR instruments, using the formula logVL=-0.27Ct+13.04, as previously reported. 16,17…”
Section: Methodsmentioning
confidence: 99%